Fiskalne stymulanty wzrostu gospodarczego w wybranych krajach Europy Środkowo-Wschodniej - Żabiński, Arkadiusz (Fiscal Growth Stimulators in the Countries of Central-Eastern Europe, 2009)
The article presents the issues of fiscal stimulus for economic growth. This problem is particularly relevant in the new EU countries that represent different approaches to the selection of fiscal policy in stimulating economic growth. The author focuses on the expenditure side of fiscal policy and analyzes the relationship between the level of budget deficit and public debt and growth. In the countries of Central-Eastern Europe, a high level of budget expenditure in relation to GDP, a high level of deficit and debt have a significant impact on reducing the pace of economic growth
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 394-404